A quasi 2D model for the interpretation of impedance and polarization of a planar solid oxide fuel cell with interconnects. (1st January 2021) - Donazzi, Alessandro; De Pascali, Stefano; Garavaglia, Francesco; Bracconi, Mauro
Highlights: A quasi 2D dynamic heterogeneous and physic model of planar HT-SOFC is presented. EIS and polarizations are simulated for SOFCs with rectangular-duct interconnects. Spatially resolved impedance spectra are simulated along the interconnect channel. Characteristic impedance features of local spectra and global spectra are revealed. Abstract: In this work, a one dimensional plus one dimensional (1D+1D) physical model of a high temperature solid oxide fuel cell (HT-SOFC) is presented. The model is distributed-charge and dynamic, and allows to predict polarization curves and impedance spectra of applicative sized planar cells (up to 10 cm x 10 cm) mounted between interconnects with rectangular ducts. The model solves rigorous conservation equations of mass, charge, momentum and energy, along the interconnect channels and within the cell's layers. The kinetic parameters of the hydrogen oxidation reaction and of the oxygen reduction reaction are fitted to a literature dataset measured between 700 °C and 800 °C, with a 20% H2, 5% H2 O and 75% N2 mixture, on a standard anode-supported HT-SOFC (Ni-YSZ/YSZ/GDC/LSCF). Once calibrated, the model is used to study the evolution of local impedance spectra along the channel, as well as the occurrence of gradients of temperature, concentration, and current density within and along the cell structure. Remarkable differences emerge between global impedance spectra, based on the average current density extracted from the whole cell's surface, and local impedance spectra, based on the local current density value at each position along the channel. Local spectra reveal very specific features (negative-resistance arcs), which are absent in the average spectra, and which question the opportunity of collecting spatially resolved impedance measurements on a fine scale. The analysis of the steady state behavior highlights the severity of temperature gradients along the channel (150 K at 0.75 V and 50% H2 utilization factor), the onset of current density peaks, and the crucial role of interphase mass transport at the gas/electrode interface. The consequences of external diffusion on the polarization performance are analyzed, and the impact of different channel configurations on the local evolution of the spectra is explored. Graphical abstract: Image, graphical abstract